Efeito da fotobiomodulação em glândulas salivares maiores, pH e bioquímica salivar de pacientes diabéticos com hipossalivação e xerostomia - Sousa, Aline Silva (2019)
Diabetes mellitus (DM) is a multifactorial chronic metabolic disease characterized mainly by the loss of glycemic homeostasis. Currently DM has a high worldwide incidence, being considered a serious health problem. In addition, several studies report other complications associated with DM that also make life difficult for patients, including problems affecting the oral cavity, such as gingivitis, periodontal disease, fungal, bacterial, viral infections, caries, hyposalivation. and xerostomia. The worsening of these manifestations is related to decreased flow and changes in salivary components, negatively impacting patients' quality of life. In order to investigate the relationship between diabetes and salivary gland dysfunction and changes in saliva composition, a randomized study was conducted with 47 patients, both genders, 18 to 65 years of age, with complaints related to oral health for example hyposalivation and xerostomia, using photobiomodulation. To detect oral manifestations, anamnesis, physical examination, salivary flow measurement, were performed by means of unstimulated and stimulated sialometry techniques, being two collections before therapy and two after, a self-perception questionnaire (OHIP). -14) was also applied. Irradiation was performed in the region of the major salivary glands, intra and extra orally, using an infrared Ecco Fibers-Quantum laser (λ = 808 nm), 120mW, 3.84J, 32s per point, being 3 extra oral and 3 bilateral intra oral points, totaling 12 points once a week for four weeks. Photobiomodulation caused significant improvement in salivary flow, in the radiometric parameters used in the group treated in the fourth week, when comparing the samples, not stimulated basal and stimulated laser, p = 0,0273. The results of calcium and total protein biochemistry showed a statistically significant change only in calcium when comparing the samples of the first and fourth week of treatment, stimulated basal and stimulated laser, p = 0,0136. It is concluded that photobiomodulation can be considered as a treatment to improve the salivary flow and composition of diabetic patients.